(untitled) (Research, Society and Development, 2021)
Fresh pasta with whole wheat flour (WWF) presents healthiness, but the consumer is not used to its consumption, due to the dark color. Therefore, the use of regional ingredients, which may change its color, could be an option to stimulate its use and daily consumption. The objective of this study was to evaluate the technological and antioxidant capacity of the fresh pasta elaborated with 51% WWF (49% Refined Wheat flour - RWF) (Control, M0) and the partial replacement of RWF by turmeric (Curcuma longa) flour (TF) at 3, 6 or 9% (respectively M1, M2 and M3). The data were analyzed by ANOVA and Tukey test (p-value<0.05). Pastes with TF presented yellowish color, longer cooking time, firmness and weight gain compared to M0. M2 presented a significant increase in total phenolics (0.57 µg Gallic Acid equivalent/mg), ABTS (12.21 µmol Trolox equivalent/mg) and DPPH (5.74 µg Trolox equivalent/mg) in relation to M0. The replacement of RWF up to 6% by TF in pastas with 51% of WWF was benefic to change color and increase functional properties, besides increasing the added-value of this tuber and promoting its consumption as healthiness and color ingredient.